Chondromalasia Patella and Torture - Ünüvar, Ümit; Zenciroğlu, Attila; İrençin, Şükran and Can, İsmail Özgür and Fincancı, Şebnem Korur and Lök, Veli (The Bulletin of Legal Medicine, 2014)
Aim: Chondromalacia patella is a syndrome characterized by degenerative changes of articular cartilage and anterior knee pain, which is common in athletes. Damage of cartilage may be the result of an acute trauma or overuse. Cartilage damage may also be a result of a direct trauma to the knee for the patients who alleged to have been subjected to torture. Although the relation between trauma and chondromalacia patella has been explicitly described in the literature, the relation to torture has not been reported previously. Aim of this study is to show that patients with a history of torture may develop chondromalacia patella. Material and Method: From 2002 to 2012, chondromalacia patella was diagnosed in 23 torture survivors among 2901 patients who were subjected to torture according to the Human Rights Foundation of Turkey’s Treatment and Rehabilitation Centers’ reports. In 10 of these patients, the symptoms started immediately after the period of torture. 13 patients whose complaints started after a sport activities or an accident were excluded from the study. The relation between trauma and chondramalacia patella was evaluated considering their history, physical and radiological findings. Findings: All patients were male. Their mean age at the time of torture was 29.7±6.72 years. Torture methods in their history were direct trauma on the knee by kicking, hitting with truncheon, jumping on the knee while the victim laying on the ground or waiting/dragging on the knee constantly. Typical complaints were anterior knee pain. Conclusion: Torture can be an etiologic factor for chondromalacia patella and it should be kept in mind in torture survivors if they have symptoms and signs and diagnostic studies should be considered. Key words: Chondromalasia; Patella; Etiologic factor; Trauma; Torture.